Cardiac resynchronization is pro-arrhythmic in the absence of reverse ventricular remodelling: a systematic review and meta-analysis. Issue 11 (14th July 2018) - Deif, Bishoy; Ballantyne, Brennan; Almehmadi, Fahad; Mikhail, Michael; McIntyre, William F; Manlucu, Jaimie; Yee, Raymond; Sapp, John L; Roberts, Jason D; Healey, Jeff S; Leong-Sit, Peter; Tang, Anthony S
Abstract: Aims: Cardiac resynchronization therapy (CRT) has been shown to reduce mortality and heart failure (HF) hospitalization but its effects on the rate of ventricular arrhythmias (VAs) appears to be neutral. We hypothesize that CRT with LV epicardial stimulation is inherently pro-arrhythmic and increases VA rates in the absence of reverse ventricular remodelling while conferring an anti-arrhythmic effect in mechanical responders. Methods and results: In this systematic review and meta-analysis, we considered retrospective cohort, prospective cohort, and randomized controlled trials comparing VA rates between cardiac resynchronization therapy-defibrillator (CRT-D) non-responders, CRT-D responders and those with implantable cardioverter-defibrillator (ICD) only. Studies were eligible if they defined CRT-D responders using a discrete left ventricular volumetric value as assessed by any imaging modality. Studies were identified through searching electronic databases from their inception to July 2017. We identified 2579 citations, of which 23 full-text articles were eligible for final analysis. Our results demonstrated that CRT-D responders were less likely to experience VA than CRT-D non-responders, relative risk (RR) 0.49 [95% confidence interval (CI) 0.41–0.58, P < 0.01] and also less than patients with ICD only: RR 0.59 (95% CI 0.50–0.69, P < 0.01). However, CRT-D mechanical non-responders had a greater likelihood of VA compared with ICD only, RR 0.76 (95% CI 0.63–0.92, P = 0.004). Conclusion: CRT-D non-responders experienced more VA than CRT-D responders and also more than those with ICD only, suggesting that CRT with LV epicardial stimulation may be inherently pro-arrhythmic in the absence of reverse remodelling.